2020
DOI: 10.1007/s00280-020-04132-x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of overall survival in patients with newly diagnosed acute myeloid leukemia and the relationship with glasdegib treatment and exposure

Abstract: Purpose Glasdegib, an oral inhibitor of the Hedgehog signaling pathway, is approved in the United States in combination with low-dose cytarabine (LDAC) to treat patients with newly diagnosed acute myeloid leukemia (AML) ineligible to receive intensive chemotherapy. This population pharmacokinetic/pharmacodynamic analysis characterized the time course of survival with glasdegib + LDAC relative to LDAC alone, and explored whether the differences in glasdegib exposure at the clinical dose of 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Smo inhibitors improve therapeutic efficacy by sensitizing dormant LSCs to chemotherapy and overcoming microenvironment-induced chemoresistance, and targeting Gli-1 also suppresses proliferation and enhances chemosensitivity in AML cells and progenitor cells [ 65 67 ]. Clinical studies have demonstrated that in combination chemotherapy, Smo inhibitor glasdegib benefits AML patients by increasing overall survival in the absence of complete remission (CR), suggesting that the antileukemia activity of glasdegib may be mediated through elimination of LSCs [ 68 70 ]. A recent study shows that the activity of Hedgehog pathway is largely independent of Smo and therefore inherently resistant to Smo inhibitors in AML, and hypomethylating agent improves glasdegib sensitivity by increasing the level of Gli-3 repressor and modulation of Gli-1 [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smo inhibitors improve therapeutic efficacy by sensitizing dormant LSCs to chemotherapy and overcoming microenvironment-induced chemoresistance, and targeting Gli-1 also suppresses proliferation and enhances chemosensitivity in AML cells and progenitor cells [ 65 67 ]. Clinical studies have demonstrated that in combination chemotherapy, Smo inhibitor glasdegib benefits AML patients by increasing overall survival in the absence of complete remission (CR), suggesting that the antileukemia activity of glasdegib may be mediated through elimination of LSCs [ 68 70 ]. A recent study shows that the activity of Hedgehog pathway is largely independent of Smo and therefore inherently resistant to Smo inhibitors in AML, and hypomethylating agent improves glasdegib sensitivity by increasing the level of Gli-3 repressor and modulation of Gli-1 [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…This significant OS improvement is reflected in a 49 % reduction in the risk of death for patients treated with glasdegib/LDAC, compared to LDAC alone. These data have been refined by treatment-response and exposure-response analyses, also specifying that variability in glasdegib exposures did not impact the risk of death (64). CR was achieved in 17 % (n = 15) and 2.3 % (n = 1) patients in glasdegib/LDAC arm and LDAC arm, respectively.…”
Section: Phase IImentioning
confidence: 99%
“…An exposure-toxicity analysis was conducted for creatine kinase increase, but no relationship was observed [ 105 , 106 ]. For glasdegib, no exposure-response relationship was seen for OS and radiological response, but exposure was significantly associated with dysgeusia, muscle spasms, renal toxicity and QTc-time prolongation ( n = 75–272) [ 107 109 ] Therapeutic drug monitoring in hedgehog pathway inhibitors could therefore primarily be of valuable in preventing excessive toxicity in patients using glasdegib [ 108 ].…”
Section: Introductionmentioning
confidence: 99%